Colors of attraction: Modeling insect flight to light behavior. Issue 8 (26th June 2018) - Donners, Maurice; van Grunsven, Roy H.A.; Groenendijk, Dick; van Langevelde, Frank; Bikker, Jan Willem; Longcore, Travis; Veenendaal, Elmar
Abstract: Light sources attract nocturnal flying insects, but some lamps attract more insects than others. The relation between the properties of a light source and the number of attracted insects is, however, poorly understood. We developed a model to quantify the attractiveness of light sources based on the spectral output. This model is fitted using data from field experiments that compare a large number of different light sources. We validated this model using two additional datasets, one for all insects and one excluding the numerous Diptera. Our model facilitates the development and application of light sources that attract fewer insects without the need for extensive field tests and it can be used to correct for spectral composition when formulating hypotheses on the ecological impact of artificial light. In addition, we present a tool allowing the conversion of the spectral output of light sources to their relative insect attraction based on this model. GRAPHICAL ABSTRACT: We present a model that estimates the number of insects attracted to a light source from its spectral output. This model facilitates better informed choices for light sources and the development of light sources that attract fewer insects.